Science fair disaster! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2016)
When his project malfunctions during the Intergalactic Science Fair, will Zack, a boy from Earth living on the planet Nebulon, be able get things under control before disaster erupts?